PENGARUH PERPUTARAN MODAL KERJA, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anya Riana Anissa, - (2019)
This study aims to determine the Effect of Working Capital Turnover (WCTO), Sales Growth, and Liquidity proxied by Current Ratio (CR). Population in this study are retail companies listed in Indonesia Stock Exchange 2013-2017. The technique of determination of the sample using the method of purposive sampling and obtained 10 retail companies with a research period of five years to obtain 50 units of samples. Data analysis was done using Microsoft Excel 2016 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 5%. The result of the research shows that (1) working capital turnover (WCTO) has a significant positive effect on profitability (ROA), (2) sales growth has significant positive effect on profitability (ROA), (3) liquidity (CR) has no significant effect on profitability (ROA).